(untitled) (Jurnal Adabiya, 2022)
Information literacy in this post-truth era is an important thing that must be understood by the Indonesian society in dealing with the truth and lies of the information obtained. This paper examines through a literature approach about the conception of information literacy in the post-truth era and what strategies must be understood by the information community in Indonesia in dealing with the spread of fake news from various media. This study concludes that critical thinking is an important part of information literacy that must be understood by Indonesian people to face the dynamics of information in the post-truth era. Critical information literacy can help our ability to search, find and use quality information. Thus, the strategy that must be carried out in dealing with the dissemination of information in the post-truth era is to identify the source, check the author, read the entire contents, check the novelty of the writing, check the balance of the information, the authenticity of the information, and always ask the experts when checking the web source.